1998
DOI: 10.1080/09593331908616770
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cadmium Adsorption from Aqueous Solution on Activated Carbon from Sugar Beet Pulp

Abstract: The adsorption ability of activated carbons from sugar beet pulp to remove the cadmium from aqueous solutions has been investigated. Optimum temperature and time for carbonization of sugar beet pulp were determined as 700°C and 120 min. The results of adsorption experiments show that pH for effectiveremoval of cadmium was 6.3 or greater. The maximum removal percentage of cadmium were found to be 99.0, 78.2 and 57.0 by. using 2.5 g j"1adsorbent dosage for initial cadmium concentration of 100, 250 and 500 mg 1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 0 publications
1
22
0
1
Order By: Relevance
“…Beet pulp is a complex material basically containing lignin and cellulose as the major constituents. Beet pulp carbon obtained from different methods to use as an adsorbent was studied for removing heavy metals such as copper and chromium ions in earlier works [19,20]. But the studies focusing on organic pollutants adsorption on beet pulp carbon and evaluating equilibrium, kinetic and thermodynamic parameters of the process are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Beet pulp is a complex material basically containing lignin and cellulose as the major constituents. Beet pulp carbon obtained from different methods to use as an adsorbent was studied for removing heavy metals such as copper and chromium ions in earlier works [19,20]. But the studies focusing on organic pollutants adsorption on beet pulp carbon and evaluating equilibrium, kinetic and thermodynamic parameters of the process are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Laszlo and Dintzis [8] have shown that the treatment of sugar beet with epichlorohydrin improved its cation exchange capacity and physical stability. In some attempts, sugar beet pulp has converted into activated carbons and investigated for heavy metals and phenol removal from aqueous solutions [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Sugar beet pulp has a respectable content of cellulose, hemicellulose and lignin, which was suitable for preparation of AC. To our knowledge, some researchers have used sugar beet pulp as starting material to prepare AC and investigated their adsorption properties (Ozer and Tumen 2003;Samadi et al 2009;Demiral and Gündüzoglu 2010;Dursun et al 2013), and few literatures focused on the separation of dyes, but only for heavy metal removal.…”
Section: Introductionmentioning
confidence: 99%